Pengaruh Penerapan Profil Pelajar Pancasila Pada Pembelajaran Ekonomi Terhadap Karakter Siswa MAN 3 Banjarmasin - Riduansyah, Riduansyah; Atmono, Dwi; Setiawan, Ananda; Rahmattullah, Muhammad (Universitas Negeri Surabaya, 2024)
This study aims to determine whether there is an influence on the application of the Pancasila Student Profile in Economic Learning on the Character of MAN 3 Banjarmasin Students. The method in this study uses quantitative research with the approach used in this study is quantitative descriptive. The subjects of the study consisted of 273 students of grade X MAN 3 Banjarmasin, the sample in this study amounted to 100 taken using Purposive sampling, a data collection technique used in the form of questionnaires to test validity and reliability through measurement model tests or outer models. Data analysis uses descriptive analysis and PLS-SEM analysis by testing structural models or inner models. The results showed that there was a significant influence between the Pancasila Student Profile on Economic Learning on the Character of MAN 3 Banjarmasin Students.